Crypto-to-Crypto Transactions: A Modern Quandary in Realisation Taxation - Allen, Christina; Parsons, Shaun (Sweet and Maxwell, 2025)
The emergence of crypto assets as a disruptive technology has created significant challenges to tax systems around the world. While both tax policymakers and academics continue to analyse the income tax consequences of new and exotic transactions, jurisdictions diverge even on the consequences of a seemingly simple transaction: the exchange of one crypto asset for another. This article considers whether there is a basis for a universal position that the exchange of crypto assets represents a realisation event. The article begins with a theoretical analysis of the accretion and realisation models of taxation. It finds that realisation is a notion used to depict a taxing point that may differ from that in accretion-based taxation, rather than a concept with its own principled definition. The article then presents the approaches of several jurisdictions with the common position that the exchange of crypto assets is a realisation event, followed by examples of jurisdictions that take a different position in specific instances, and the rationale underlying those positions. Having established that there is no universal basis for establishing the occurrence of a realisation event, and that jurisdictions may justifiably and indeed do differ in their positions, the article considers both theoretical and practical arguments for and against the recognition of a realisation event arising from the exchange of crypto assets. The article concludes by proposing what may be a theoretically defensible and pragmatic way forward to guide the taxation of crypto asset exchanges.